Students’ perceptions of the relevancy of marketing education - Audrey Malenee,; Choy, Siew Chee (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
It is interesting to note that many tertiary institutions have started to incorporate marketing courses in their various programmes in order to fulfil the demands of today’s competitive industry. Marketing courses play a vital part in business as well as non-business programmes. However, students’ reactions to such courses have not been well studied. Most marketing education studies have focused mainly on the teaching methodologies without giving due consideration to students’ perceptions of such courses. There is a dearth of research into students’ perceptions of the relevancy of marketing education, specifically in the Malaysian context. Added to this, there is also a need to determine possible links between student’s perceptions and their performance in a marketing course. Studies have shown that students place more effort in learning when they view the subject matter as relevant to their future careers. For this study, data was gathered from a cohort of eighty students consisting of those who majored in marketing and those who had marketing as a course in their programme of study. Analysis of perceptions showed that students who majored in marketing favoured these courses more and mostly outperformed non-marketing majors.